Perbandingan Pendekatan Breadth First Search, Depth First Search dan Best First Search Pada Pencarian Rute Menggunakan Metode Branch and Bound - Ryano Alderio; Rianita Puspa Sari (Fakultas Teknik, 2023)
A Travelling Salesman often encounters a problem where they have to find the shortest route that can be passed when they want to visit several places without having to go to the same place more than once. So, it is necessary to find the shortest route that is useful for efficient distribution. The Travelling Salesman Problem is solved using the branch and bound method with three different approaches: Breadth First Search, Depth First Search, and Best First Search. These three approaches will be compared regarding their effectiveness and efficiency. The case study used is a team of cigarette product sellers in the Kuningan area who will distribute their products to four villages. The route currently in use is from Warehouse → Karangmangu Village → Jalaksana Village → Peusing Village → Sidamulya Village → Warehouse with a distance of 19,8 km. The result of this study obtained the shortest route with the path from Warehouse → Karangmangu Village → Sidamulya Village → Peusing Village → Jalaksana Village → Warehouse with a distance of 19,7 km. And the comparison result obtained is that The Breadth First Search approach requires more calculations with 28 calculations, while The Depth First Search approach requires 25 calculations, and The Best First Search approach requires 23 calculations.